Essential Effects on the Mobility Extraction Reliability for Organic Transistors. (30th August 2018) - Xu, Yong; Sun, Huabin; Liu, Ao; Zhu, Huihui; Li, Binhong; Minari, Takeo; Balestra, Francis; Ghibaudo, Gerard; Noh, Yong‐Young
Abstract: The reliability of mobility has come to be a critical issue to the development of new electronics especially for organic electronics, since mobility is typically extracted from field‐effect transistors containing various extrinsic effects and overestimation is popular in the literature. Recently, this issue is emphasized and a reliability factor ( r ) is proposed by pioneers to gauge the mobility reported. Albeit many factors discussed, how much the extrinsic effects influence r remains unrevealed and a facile solution by using organic transistors is still lacking. Here, it is shown that the widely used extraction method based on the saturation transfer characteristics is sensitive to contact effect and temperature with r dropping to 43%, indeed leading to large mobility overestimation. By contrast, the linear‐regime methods are more reliable particularly the Y‐function method that demonstrates great reliability ( r ≈ 100%) even for short‐channel transistors at ultralow temperatures. In addition, operating in saturation regime induces ambipolar conduction further deteriorating reliability if contact doping is absent. High Schottky barriers, on the other side, distort device characteristics making extraction impossible. The results of this study reveal that, aside from device optimizations, selecting a right method is essential for reliable and precise evaluation of the carrier mobility by using organic transistors. Abstract : This paper systematically addresses the essential effects on the mobility extraction reliability . The effects related to specific dielectric capacitance, operating regime, channel length, temperature, ambipolar conduction, and Schottky barrier are examined in a quantitative way. The results of this study show that, aside from device optimizations, selecting a proper extraction method is important to reliable mobility evaluation using organic transistors.